Diversi Sebagai Aplikasi Restorative Justice Dalam Sistem Peradilan Pidana Anak Di Indonesia - tri susilowati (Justicia Journal, 2012)
As we know, that there is a real act of dr aspect there is no difference between criminal do not minors with criminal offenses committed by adults. Which can distinguish between the two is on the perpetrators themselves.The difference involves the question of motivation for their actions. Judging from the motivation to do a crime, in general, a child who commits an offense is not based on the motivation of evil (evil mill / evil mind) who came dr child itself.On the basis of that, children who deviate from social norms, to their understanding as the "bad boy" or the term "Juvenil Deliquency".Based on UU No. 11 Year 2012 on the Criminal Justice System Son, so that the child's dignity as human beings; then the child should be given special protection, especially protection law in the juvenile justice system.Therefore, in order to children in conflict with the law (ABK) can be well protected, then one of them different ways of treatment pursued through the Restorative Justice Diversion process.